TaER Expression Is Associated with Transpiration Efficiency Traits and Yield in Bread Wheat. - Jiacheng Zheng; Zhiyuan Yang; Pippa J Madgwick; Elizabete Carmo-Silva; Martin A J Parry; Yin-Gang Hu (PLoS ONE)
ERECTA encodes a receptor-like kinase and is proposed as a candidate for determining transpiration efficiency of plants. Two genes homologous to ERECTA in Arabidopsis were identified on chromosomes 6 (TaER2) and 7 (TaER1) of bread wheat (Triticum aestivum L.), with copies of each gene on the A, B and D genomes of wheat. Similar expression patterns were observed for TaER1 and TaER2 with relatively higher expression of TaER1 in flag leaves of wheat at heading (Z55) and grain-filling (Z73) stages. Significant variations were found in the expression levels of both TaER1 and TaER2 in the flag leaves at both growth stages among 48 diverse bread wheat varieties. Based on the expression of TaER1 and TaER2, the 48 wheat varieties could be classified into three groups having high (5 varieties), medium (27 varieties) and low (16 varieties) levels of TaER expression. Significant differences were also observed between the three groups varying for TaER expression for several transpiration efficiency (TE)- related traits, including stomatal density (SD), transpiration rate, photosynthetic rate (A), instant water use efficiency (WUEi) and carbon isotope discrimination (CID), and yield traits of biomass production plant-1 (BYPP) and grain yield plant-1 (GYPP). Correlation analysis revealed that the expression of TaER1 and TaER2 at the two growth stages was significantly and negatively associated with SD (P<0.01), transpiration rate (P<0.05) and CID (P<0.01), while significantly and positively correlated with flag leaf area (FLA, P<0.01), A (P<0.05), WUEi (P<0.05), BYPP (P<0.01) and GYPP (P<0.01), with stronger correlations for TaER1 than TaER2 and at grain-filling stage than at heading stage. These combined results suggested that TaER involved in development of transpiration efficiency -related traits and yield in bread wheat, implying a function for TaER in regulating leaf development of bread wheat and contributing to expression of these traits. Moreover, the results indicate that TaER could be exploitable for manipulating important agronomical traits in wheat improvement.